1997
DOI: 10.1023/a:1026487609215
|View full text |Cite
|
Sign up to set email alerts
|

A C-terminal domain of HIV-1 accessory protein Vpr is involved in penetration, mitochondrial dysfunction and apoptosis of human CD4+ lymphocytes

Abstract: We have previously shown that expression of HIV-1 vpr in yeast results in cell growth arrest and structural defects, and identified a C-terminal domain of Vpr as being responsible for these effects in yeast. In this report we show that recombinant Vpr and C-terminal peptides of Vpr containing the conserved sequence HFRIGCRHSRIG caused permeabilization of CD4+ T lymphocytes, a dramatic reduction of mitochondrial membrane potential and finally cell death. Vpr and Vpr peptides containing the conserved sequence ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 55 publications
0
62
0
Order By: Relevance
“…Vpr was shown to cause cell cycle arrest and apoptosis in T cells (9,27). To determine whether monocytic cells exposed to Vpr peptides undergo apoptosis, THP-1 cells were treated with Vpr-(52-96) or Vpr-(1-45) peptides for 24 h followed by measurement of apoptosis.…”
Section: Vpr-(52-96) Peptide Induces Apoptosis Through the Mitochondrmentioning
confidence: 99%
See 1 more Smart Citation
“…Vpr was shown to cause cell cycle arrest and apoptosis in T cells (9,27). To determine whether monocytic cells exposed to Vpr peptides undergo apoptosis, THP-1 cells were treated with Vpr-(52-96) or Vpr-(1-45) peptides for 24 h followed by measurement of apoptosis.…”
Section: Vpr-(52-96) Peptide Induces Apoptosis Through the Mitochondrmentioning
confidence: 99%
“…The amino acid sequence of these peptides is as follows: Vpr-(52-96), DTWAGVEAIIRILQQ-LLFIHFRIGCRHSR IGVTRQRRARNGASRS; Vpr-(1-45), MEQAPEDQGPQREPYNEWTLELLEELKSEAVRHFPRIW-LHNLGQH. Because of the high propensity of Vpr peptides to bind to proteins, cells (1 ϫ 10 6 /ml) were treated with peptides in an isotonic buffer (13 mM HEPES, 2.4% glucose, 68 mM NaCl, 1.3 mM KCL, 4 mM Na 2 HPO 4 , 0.7 mM KH 2 PO 4 , pH 7.2) for 30 min followed by addition of culture medium as described previously (27).…”
Section: Isolation Of Monocytes From Peripheral Blood Mononuclearmentioning
confidence: 99%
“…All of the peptides tested contained a motif, designated H (F/S) RIG, which has been previously identified as mediating the penetration of Vpr into CD4 + lymphocytes with concomitant induction of mitochondrial dysfunction and apoptosis. 61 Although all of the peptides contained this motif, not all of these peptides mediated equivalent inhibition of B16.F10 proliferation. In fact, as indicated above, the more carboxy of these peptides, within the 65-91 amino acid region, inhibited proliferation progressively less than the more amino fragments.…”
Section: Discussionmentioning
confidence: 98%
“…Mapping studies performed on isolated mitochondria revealed that the N-terminal 1-51 aa of Vpr, Vpr , are vital for virion incorporation and nuclear localization, whereas the Cterminal 52-96 aa, Vpr , induce cell-cycle arrest and apoptosis (11,17,19,20). Vpr can cause apoptosis either upon infection with Vpr-expressing HIV isolates or following exposure of cells to the purified protein (14,15,21). We and others have shown that this apoptotic effect is mimicked by Vpr but not by the Vpr(1-51) moiety (13,22).…”
mentioning
confidence: 99%